Partners in the Arctic : Student-driven health promoting activities in northern Sweden - Kostenius, Catrine (Luleå tekniska universitet, Hälsa och rehabilitering, 2013)
The point of departure was the interest in partnering with students inviting them to be actively part of health promotion efforts in school to examine what possible benefits partnerships with students can offer and ways of implementation. The aim was to examine how studentsin the arctic region of the world experienced creating, leading and participating in student-driven health promoting activities in cooperation with their teacher. Inspired by the PAAR method (participatory appreciative action research) 19 Swedish students, ages 10 - 11 participated in health promotion work in school.The questions posed to the students were - What makes you feel good in school? - If you got to decide what health promoting activities to do what would be your choice?Then they participated through creating, leading, participating in and evaluating their own and their peers’ health promoting activities. The student’s health promoting activities included tools such as music, massage, physical activity and the outdoors . The comprehensive understanding of how students in the arctic region of the world experienced creating, leading and participating in student - driven health promoting activities in cooperation with their teacher, revealed three key points; i) When students were asked to choose health promoting activities, they were not only in line with existing research but were able to reflect on how to develop praxis, ii) Students are competent to lead health promoting activities with the support of their teacher and participating in health promoting activities lead by their peers, iii) The group assignment in this study offer one example of implementing health promoting activities in school to increase health literacy. This study can serve as an example of viewing students as partners and giving them voice and space in health promotion and the concept of the “Arctic gate” for health promotion is suggested. Godkänd; 2013; 20130306 (andbra)